2016
DOI: 10.1186/s40893-016-0007-x
|View full text |Cite
|
Sign up to set email alerts
|

Stroop event-related potentials as a bioelectrical correlate of frontal lobe dysfunction in multiple sclerosis

Abstract: Background: Dysfunction of higher cognitive abilities occurs in 40-60 % of people with multiple sclerosis (MS), as detected with neuropsychological testing, with predominant involvement of executive functions and processing speed. Event-related potentials to the Stroop are a bioelectrical correlate of executive function. We tested whether event-related potentials to the executive Stroop test may reflect executive dysfunction in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Correspondingly, fMRI studies on age-related differences in emotional processing have shown that, given available cognitive resources, older adults show greater rACC activities than younger adults in happy faces trials ( Brassen et al, 2011 ). Moreover, brain activity in the ACC is linked to age-related PE, and the increment in prefrontal activity in older adults seems to be an indicator of compensatory improvement in cognitive control ability or impairment mechanism in intracortical inhibition ( Amato et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, fMRI studies on age-related differences in emotional processing have shown that, given available cognitive resources, older adults show greater rACC activities than younger adults in happy faces trials ( Brassen et al, 2011 ). Moreover, brain activity in the ACC is linked to age-related PE, and the increment in prefrontal activity in older adults seems to be an indicator of compensatory improvement in cognitive control ability or impairment mechanism in intracortical inhibition ( Amato et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%